The Role of Peer Social Support in Reducing Adolescent Antisocial Behavior: A Study of Senior High School Students in Tomohon City - Anggrian, Riki; Kasenda, Rinna Yuanita; Kamal, Luluk Syahrul (Jurnal Ilmu Sosial dan Humaniora, 2025)
Antisocial behavior among senior high school students manifested through behaviors such as aggression, rule violations, social withdrawal, and lack of empathy poses challenges to socio-emotional development and school climate. Peer social support has been identified as a protective correlate of adolescent behavior, yet evidence from specific local contexts remains limited. This study aimed to describe (1) the level of antisocial behavior tendencies, (2) the level of peer social support, and (3) the relationship between peer social support and antisocial behavior among senior high school students in Tomohon City. Employing a quantitative correlational design with a cross-sectional approach, data were collected from 533 students selected through cluster sampling. Antisocial behavior and peer social support were measured using self-report scales with satisfactory reliability (Cronbach’s α = .84 and .84, respectively). Descriptive analysis indicated low to moderate antisocial behavior tendencies and moderate to high peer social support. Pearson correlation analysis revealed a significant negative relationship between peer social support and antisocial behavior (r = −0.23, p < .001), indicating that students who perceived higher peer support tended to report lower antisocial tendencies without implying causality. These findings highlight the relevance of peer-based preventive strategies such as peer mentoring and structured peer-support groups particularly within the communal socio-cultural context of Tomohon City, where peer interaction plays a central role in adolescents’ daily school life.